Measures of Performance in the Context of International Social Ventures: An Exploratory Study. Issue 1 (2nd January 2016) - Chmelik, Erin; Musteen, Martina; Ahsan, Mujtaba
Abstract: This study reviews literature on performance measures among international social ventures and draws interviews with 12 US social ventures to explore how the use of such measures varies depending on the type of social venture, its funding business model, and scale of operations. We find some distinct differences in the use of performance measures among the different types of social enterprises related to the focus on stakeholders, emphasis on inputs, outputs, and outcomes. Implications for theory and practice of social entrepreneurship are discussed.